Prediction and Measurement of the local extinction coefficient in sprays for 3D simulation/experiment data comparison - Grosshans, Holger; Kristensson, E.; Szász, R. -Z.; Berrocal, E. (International journal of multiphase flow, 2015)
In the recent years, large progresses in laser imaging techniques have allowed to extract spatially resolved 2D and 3D quantitative spray information even in optically dense situations. The main breakthrough of these techniques is the possibility of suppressing unwanted effects from multiple light scattering using Structured Illumination. Thanks to this new feature, effects due to light extinction can also be corrected allowing the measurement of the local extinction coefficient. These quantitative information which is available even in challenging conditions, where Phase Doppler does not work anymore, can be used for data comparison between experiment and simulation. The local extinction coefficient is particularly valuable for the description of the droplet field, defined as the “spray region”, as it contains information related to both droplets size and concentration. In this article we detail, then, the procedure enabling the modelers to obtain numerically this local extinction coefficient over the full 3D spray system. Following this procedure, results can now be adequately compared between simulation and experiment. The proposed comparison approach can better guide model adjustments in situation where the initial droplet size distribution is unknown or approximated and presents a step towards future validations of spray simulations, especially those based on Lagrangian Particle Tracking. The approach is exemplified here for the case of a Diesel-type spray. The results reveal at which specific spray locations discrepancies occur, and highlight the sensitivity of the initial droplet size distribution on the resulting extinction coefficient.
Gesehen am 12.01.2021